Exploring the origin and fate of surface and sub-surface marine microplastics in the Canary Islands region - Vega-Moreno, Daura; Sicilia-González, Sergio; Domínguez-Hernández, Cristopher; Moreira-García, Enedina; Aguiar-González, Borja; Hernández-Borges, Javier; Fraile-Nuez, Eugenio; Machín, Francisco (Frontiers in Marine Science, 2024)
The presence of different types of microplastics (MPs) in the Atlantic Ocean has been well-documented, with data collected from the Canary Islands indicating high concentrations of MPs at four different beaches (hot spots). However, critical gaps persist regarding the abundance of MPs in diverse open ocean regions, at varying depths, and their transport behavior and origin. This study aims to evaluate, for the first time, the large-scale (>100 km) and mesoscale (10-100 km) ocean dynamic processes and the resulting transport of MPs in the region. On the one hand, this study investigates the surface velocity of currents between 27-32°N latitude range, establishing correlation with the accumulation of MPs on diverse beaches across several islands of the archipelago. This analysis goes beyond studying the predominant current by integrating data at a smaller geographical scale over a two-year period. Concurrently, previous and ongoing research suggests the presence of small MPs (SMPs,<1 mm) at high concentration at a depth of 1100 meters in this region. By integrating these vertical profiles of MPs with a deep understanding of the physical processes of the Canary region accumulated over decades of research, our study introduces an innovative model that outlines how SMPs are sink and transported in open oceans by water mases. This comprehensive approach not only enhances our understanding of the complex dynamics influencing the distribution of MPs but also provides crucial insights to address the widespread problem of MP pollution in the Atlantic.